Human Rights in Higher Education Institutional, Classroom, and Community Approaches to Teaching Social Justice (Palgrave Studies in Global Citizenship Education and Democracy, 2018)
This book focuses on human rights education (HRE) in higher education, with an emphasis on supporting undergraduate education for social justice and global citizenship at the institutional, classroom, and community levels. Drawing from the work of human rights scholars and advocates at Webster University, Kingston begins a critical discussion about the potential of HRE on college campuses and beyond. Chapter contributors address the institutional issues inherent to building a "human rights campus," promoting just governance models, facilitating student research, and fostering inclusive campus communities. They further explores opportunities within the classroom by highlighting dynamic courses on global sustainable development and post-genocide reconciliation in Rwanda, as well as considering how to create trauma sensitive learning spaces and utilize photography as a human rights teaching tool. Finally, scholar-advocates detail how HRE can be expanded to include the broader community-including teaching critical criminology to aspiring police officers, facilitating community dialogue through academic conferences, and engaging in social justice work related to access to justice, domestic violence, and human trafficking.